P-200 An addition of nicotinamide adenine dinucleotide (NAD+) precursor to oocyte maturation medium improves the developmental competence of bovine oocytes after IVF. (30th June 2022) - Hashimoto, S; Kankanam Gamage, U; Morimoto, Y
Abstract: Study question: Does an increase of nicotinamide adenine dinucleotide (NAD + ) level in oocytes lead to an improvement of blastulation after IVF? Summary answer: The addition of NAD + precursor to the oocyte maturation medium increased NAD + levels in the oocytes, improving the developmental competence to the blastocyst after IVF. What is known already: With maternal ageing, the enzyme that degrades NAD + (CD38) increases in cells and the amount of NAD + in cells, including oocytes, decreases. The degradation of NAD + is also increased when cells are isolated from tissues. NAD +, which is an electron carrier used by all eukaryotes, is reduced to NADH via beta-oxidation of fatty acids and the TCA cycle, enhancing ATP synthesis in the mitochondrial electron transfer system. In addition, an enzyme in the inner mitochondrial membrane donates protons from NADH to NADP + to synthesize NADPH, which maintains the intracellular redox state. Study design, size, duration: This study is a prospective study using bovine oocytes retrieved from ovaries obtained from a local slaughterhouse in Osaka city. A total of 2, 501 bovine oocytes were used in this study. Participants/materials, setting, methods: Bovine cumulus-oocyte-complexes (COCs) were matured in vitro in the culture (IVM) medium supplemented with 0-100 μM nicotinamide mononucleotide (NMN). Matured oocytes were inseminated with the washed spermatozoa and cultured to assess the blastulation. Matured oocytes were also used to examine their NAD +, reactive oxygen species (ROS) and ATP levels. Main results and the role of chance: The addition of NMN to the IVM medium increased intracellular NAD + levels of bovine mature oocytes at 1 µM and above. As a result, it increased intracellular ATP levels and decreased ROS levels at 10 µM and above. It also improved blastocyst formation rates after IVF at 100 µM (P < 0.05; 35%) compared with control (22.2%). Moreover, the supplementation of NMN to the IVM medium decreased the percentage of apoptotic cells and intracellular ROS levels in cumulus cells surrounding oocytes. Limitations, reasons for caution: This study was conducted in vitro using bovine oocytes. Thus, studies using human samples should be performed before clinical application. Wider implications of the findings: By replenishing NAD +, we have found a clue to improving the IVM and IVF outcome, which has been shown to have a lower blastocyst formation rate than conventional IVF methods using in vivo matured oocytes. It may also improve the developmental potential of oocytes retrieved from older women. Trial registration number: not applicable